Case series: Osteonecrosis of the jaw related to denosumab preceded by bisphosphonates in cancer and osteoporotic patients - Devie Falinda; Nicholas Malden (Advances in Oral and Maxillofacial Surgery, 2022)
Aims: The purpose of this study was to assess the incidence of medication-related osteonecrosis of the jaw (MRONJ) in cancer and osteoporotic patients taking denosumab (DSB) preceded by bisphosphonates (BP). Methods: The data collection tool was adapted from the American Society of Bone and Mineral Research (ASBMR) consisting of patient details, comorbidities, clinical history, dose, and duration of DSB and preceding BP, diagnosis and MRONJ stage, management and outcomes. The staging of MRONJ follows recommendations of the American Association of Oral and Maxillofacial Surgeons (AAOMS). This retrospective case series used data from seven patients treated at the Department of Oral Surgery, Edinburgh Dental Institute over a one-year period. Results: All patients had a history of bisphosphonate therapy prior to commencement of denosumab therapy. One out of 7 showed no development of osteonecrosis of the jaw yet was categorized as a high-risk case. Of the remaining six cases, osteonecrosis of the jaw was present as stage 2 in four cases and stage 3 in 2 cases. Four cases developed MRONJ 8 weeks after dental extraction. The remaining two cases developed MRONJ at 12 and 20 weeks after extraction. Conclusions: The main conclusion of this study is the potentially cumulative effect of BP and DSB in the development of MRONJ with dental extraction as a triggering factor. Further research is required before the cumulative effect of these anti-resorptive agents become fully understood.